PENGARUH TOLERANSI BERAGAMA TERHADAP INTERAKSI SOSIAL PADA SMK KESEHATAN SAHATA, PEMATANGSIANTAR - Harmonvikler Dumoharis Lumbanraja; Donald Loffie Muntu (Jurnal Theologia Forum STFT Surya Nusantara, 2019)
Tolerance is one of the crucial problem in the social life, where the variety of community aspect become the separating wall between the individual, creating disharmony and intolerance, that cause social friction and dislike to each other. Religion intolerance is a national problem where the people who cling to a religion and belief could have friction in the social life. This research is to determine the influence of religion tolerance toward social interaction among high school student in SMK Kesehatan Sahata in Pematangsiantar, North Sumatera. The research is empirical, the sampling technique used was problability sampling focused on simple random sampling, and the formula of Slovin to determine the number of respondents. Variables were used are entered/removed to explain the variable entered and method used. Data analysis was used using simple linear regression to explain the correlation/relationship (R) as 0.563. The result of determinant coefficient (R Square) was 0.317, that interpreted the influence of independent variable (religion tolerance) toward the dependence variable (social interaction) was 31.7%. The study concludes that religion tolerance has influence toward social interaction among high school students in SMK Kesehatan Sahata.